Evaluation of Factors Regarding Misuse of Antimicrobials in Poultry and Piggery Farms in Abia State, Nigeria (Global Journal of Medical Research, 2014)
A survey was conducted to evaluate the factors that can cause misuse or abuse of antimicrobials in poultry and piggery farms. This evaluation was conducted between May 2011 and April, 2012 using a structured questionnaire distributed by the author to farm managers. The results showed that level of education of farm managers have a role to play in prudent use of antimicrobials. Only a small percentage (10% for poultry,20% for piggery farms) of antimicrobial prescriptions were made by veterinarian, while the key prescriptions (70% poultry, 60% piggery farms) were made by the farmers or the farm managers. Laboratory analysis was not routinely done on samples before antimicrobial administration. Majority of antimicrobial administration (45% for poultry farms, 60% for piggery farms) were based on history of disease and mere observations on the animals. In the poultry farms, 60% of farm managers have degree and they adhered to the average of 3-4 days (65%) duration of antimicrobial administration. The results showed that majority of antimicrobial administrations were made by farm managers with minimal laboratory analysis of samples. It is anticipated that this findings will create awareness on the appropriate use of antimicrobials on farm animals.
Keywords: antimicrobial misuse; poultry farms; piggery farms; evaluations